2013
DOI: 10.1039/c3sm51955d
|View full text |Cite
|
Sign up to set email alerts
|

Stability of discoidal high-density lipoprotein particles

Abstract: Motivated by experimental and numerical studies revealing that discoidal high-density lipoprotein (HDL) particles may adopt flat elliptical and nonplanar saddle-like configurations, it is hypothesized that these might represent stabilized configurations of initially unstable flat circular particles. A variational description is developed to explore the stability of a flat circular discoidal HDL particle. While the lipid bilayer is modeled as two-dimensional fluid film endowed with surface tension and bending e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 28 publications
(80 reference statements)
1
20
0
Order By: Relevance
“…It can then be shown that f n ¼ 0 and f n ¼ s. These results are consistent with previous findings of, e.g., Maleki & Fried (2013b). The force and bending moment that S exerts on C are À ( f n n þ f n n) and À (m e e þ m n n), respectively.…”
Section: Force and Bending Moment Exerted By An Open Lipid Bilayer Onsupporting
confidence: 92%
“…It can then be shown that f n ¼ 0 and f n ¼ s. These results are consistent with previous findings of, e.g., Maleki & Fried (2013b). The force and bending moment that S exerts on C are À ( f n n þ f n n) and À (m e e þ m n n), respectively.…”
Section: Force and Bending Moment Exerted By An Open Lipid Bilayer Onsupporting
confidence: 92%
“…Although the effect of this additional symmetry break of the model could most likely also have been obtained by other means, e.g., through introduction of saddle-splay deformations, the appearance of a lense shape introduces only one more fit parameter and is furthermore in good accordance with an expected pinching effect at the rim of the disks due to interactions between the lipid bilayer and the ApoA1-protein (34). We refer to the literature for more elaborate discussions on out-of-plane geometry of lipid bilayers (34,35). The histidine tags of truncated ApoA1 protein as well as the N-terminal domain of ApoA1 were modeled as Gaussian random chains in agreement with previous findings (3).…”
Section: Modeling Of Saxs Datamentioning
confidence: 63%
“…Substituting equation ( 22) into equation (20) yieldṡ…”
Section: Tangential Variationsmentioning
confidence: 99%
“…A classic example is the loss of stability in membrane tubules, known as the pearling instability [18,19]. The stability of flat discs has been recently studied in the context of high density lipoproteins [20] and disc-to-vesicle shape transition [21]. While these studies have given fundamental insights into the stability of homogeneous membranes with quadratic energy, there is a need to extend the framework to study systems with heterogeneous properties and higher-order bending energies.…”
Section: Introductionmentioning
confidence: 99%